Study of Mechanical Properties and Microstructure of Mercedes-Benz and Local Radiator Material - Usman Sudjadi; Rahmad Jayadiningrat; Erwan Hermawan; Agus Jamaludin (Jurnal Fisika Indonesia, 2020)
Indonesia has the capability to produced local products such as vehicle radiators. Many studied were carried out to characterize the radiator material. But it still needs to compare local products and imported products. This study carried mechanical properties and microstructure analysis for Marcedes Benz's core radiator and local radiator. The tools used in this study are microhardness tools, optical microscopes, and XRF. The result shows that the Mercedes-Benz radiator binding material before the heat treatment process, using an optical microscope shows the invisible results of a collection of atoms and the matrix and grain boundaries. On local radiator material, Not yet seen the collection of atoms and matrix and grain boundaries. White grains of Mercedes Benz radiator material is more abundant than local radiator materials. Chemical composition test results are; local radiator material content is dominated by three elements Ca (26.3%), Zn (44.4%) and Cu (13.9%) Cu (2.48%), Fe (45.15%), and Mn (44.88%). The German Mercedes-Benz element contents are; Fe (28.7), Mn (27.5), Ca (39.2). The hardness of the Mercedes-Benz radiator before heating is 43.4 HV, after being heated 39.2 HV. The hardness local radiator material before heating 43.5 HV and after heating 38.2 HV.